METHOD FOR DETERMINING WORKING REGIME WITH REASONABLENESS OF EQUIPMENT CASING PIPE BY ROTARY PRESS – IN - Pham Van, Minh; Pham Quang, Dung (Journal of Applied Engineering Science, 2022)
Accroding to the surveyed data of soil mass in Cone Penetration Test (CPT), the research paper defines drag on steel casing pipe used for constructing bored pile by rotary Press – in method, through that, the paper designs the way of defining the working regime with reasonableness of equipment casing by rotary Press – in method, which will be regarded as a neccessary step to design the installation of the equiment on the available base machine in Vietnam with the intention of not only maximizing the capacity of transmissing but improving the machine’s productivity. It makes a contribution in reduce in the investment’s costs and increase in effective exploitation of this equipment in Vietnam.
Keywords: equipment casing, rotary press – in method, base machines, reasonable working regimes